Faktor-Faktor Yang Mempengaruhi Minat Perilaku Wajib Pajak Untuk Menggunakan E-Filling(Studi Empiris Pada Wajib Pajak Orang Pribadi Di Kota Surakarta) - Haryanti, Wiwin; , Dra. Mujiyati, M.Si (2016)
ABSTRACT The purposes research aimed to know the effect of the usefulness perception, the easiness perception, volunteerism, social factor, safety and secrecy for the tax payer interest behaviors to use e-filling. The population in this research includes all of individual tax payers in Surakarta who use e-filling. The researcher used convenience sampling, with the total sample of 100 tax payers. The data was used in this research is primary data by using questionnaire. The data was analyzed by using quality test data (validity and reliability tests), classic assumption test (normality test, multicolinierity test, and heteroscedasticity test), multiple linear regression test, coefficient of determination, F test, and t test. Result showed that, the usefulness perception, the easiness perception, volunteerism, social factor, safety and secrecy have significant effect for the tax payer interest behaviors to use e-filling. Keyword: interest, tax payer, e-filling, technology acceptance model (TAM)